2019
DOI: 10.3390/bs10010011
|View full text |Cite
|
Sign up to set email alerts
|

Strangers, Friends, and Lovers Show Different Physiological Synchrony in Different Emotional States

Abstract: The mere copresence of another person synchronizes physiological signals, but no study has systematically investigated the effects of the type of emotional state and the type of relationship in eliciting dyadic physiological synchrony. In this study, we investigated the synchrony of pairs of strangers, companions, and romantic partners while watching a series of video clips designed to elicit different emotions. Maximal cross-correlation of heart rate variability (HRV) was used to quantify dyadic synchrony. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 55 publications
2
32
0
Order By: Relevance
“…Moreover, due to its putative role for adaptive dyadic functioning, interpersonal synchrony has been studied in human dyads such as mother and infant (Davis et al., 2018; Feldman et al., 2011), therapist‐patient (Tschacher & Meier, 2019), romantic partners (Cacioppo et al., 2014; Coutinho et al., 2018; Reed et al., 2013), and even strangers (Bizzego et al., 2020; Tschacher et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, due to its putative role for adaptive dyadic functioning, interpersonal synchrony has been studied in human dyads such as mother and infant (Davis et al., 2018; Feldman et al., 2011), therapist‐patient (Tschacher & Meier, 2019), romantic partners (Cacioppo et al., 2014; Coutinho et al., 2018; Reed et al., 2013), and even strangers (Bizzego et al., 2020; Tschacher et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4 top-left visualizes an example pair of time-normalized IBI series. This effectively resamples the IBI series at 2 Hz as has been done in prior research ( Golland et al , 2015 ; Bizzego et al , 2020 ) in which linear interpolation was shown to have better performance for time-domain and high-frequency variability compared with other interpolation measures ( Choi and Shin, 2018 ). Heart rate variability measures, typically extracted from the IBI series, are parsed into the following frequency bands: ultra-low frequency (≤ 0.003 Hz), very low frequency (0.0033–0.04 Hz), low frequency (0.04–0.15 Hz), and high frequency (0.15–0.4 Hz) ( Shaffer and Ginsberg, 2017 ).…”
Section: Physiological Data Set For Demonstrating Methodsmentioning
confidence: 99%
“…F 1 is associated with the components in the signals that convey the information about the heart beats (the QRS complexes in the ECG and the pulses in the BVP); F 2 is the band which contains all the main frequency components of the signals. For ECG signals: F 1 = [5, 14] Hz, F 2 = [5, 50] Hz , [29]; for BVP signals: ( F 1 = [1, 2.25] Hz, F 2 = [0, 8] Hz [18]). ψ is expected to have values 0.5 ≤ ψ ≤ 0.8 [29].…”
Section: Methodsmentioning
confidence: 99%
“…Many scientific fields would benefit from the adoption of WDs for long-term, unobtrusive recording of physiological signals. In particular, scientific use of WDs is explored in affective computing [37, 35], research on autism [46, 26], interpersonal coupling [3, 8] and psychology in general.…”
Section: Introductionmentioning
confidence: 99%